The Game of Identity Politics: Delta Airlines Performs Neutrality - Perez, James (Journal of Management Policy and Practice, 2019)
The language used by Delta Airlines in a press release when responding to the controversial topic of gun control given the Parkland Mass Shooting is examined. Delta Airlines uses several linguistic techniques to perform neutrality on the polarizing issue of gun regulation. The techniques involve referring to themselves in the third person, simple grammatical structures, and objective lexical choices. A brief discussion regarding the efficacy of the press release by Delta follows the analysis. Several headlines from major news organizations are examined to discuss how journalists linguistically use emotionally charged language to represent the airline.